Anti-inflammatory activity of the apolar extract from the seaweed Galaxaura marginata (Rhodophyta, Nemaliales) - E. Rozas; J. C. Freitas (Journal of Venomous Animals and Toxins including Tropical Diseases, 2007)
The red seaweed Galaxaura marginata (Ellis & Solander) Lamouroux, well known by the antibacterial activity of its polar extract and the cytotoxic activity of its oxygenated desmosterol, showed anti-inflammatory action in its apolar fraction. Topical anti-inflammatory activity was observed in samples collected at São Sebastião channel, northern littoral of São Paulo State, Brazil. The apolar extract and its fractions obtained through Thin-Layer Chromatography (TLC) reduced the topical inflammation produced by croton oil in mouse ear. Such data indicated that the apolar extract from the marine red alga G. marginata displayed anti-inflammatory activity (since 1mg/ear extract reduced 95±0.5% inflammation), which could be the result of the synergic activity of the four fractions present in the apolar extract.